(untitled) (Eurasian Research Bulletin, 2023)
The development of scientific and technological progress, changes in the sphere of production at modern industrial enterprises, including the task of ensuring the safety of workers in production, including the development of special clothing for their protection, first of all optimally solve the tasks set, the problem of the harmful effects of the production environment puts it in first place. In modern economic conditions, the problem of purposeful improvement of the assortment and quality of special clothes that adequately satisfy the needs of customer organizations is of particular importance. Personal protective equipment (PPE) has a special place in the complex of measures to ensure the safety of workers and prevent occupational diseases. Among the widely used personal protective equipment is special clothing, which is one of the necessary conditions for reducing the impact of dangerous and harmful production factors on a person and maintaining high performance and health.